Estudo eco-hidrológico da bacia hidrográfica Mariana, afluente do Rio Taxidermista, Alta Floresta - MT - Umetsu, Ricardo Keichi (Universidade Federal de São Carlos, 2009)
This study aimed to describe the hydro-ecological aspects of Mariana Hydrographic Basin, tributary of the river Taxidermista, Alta Floresta, MT, Brazil. Therefore, studies were performed on the morphometry of the basin; land use; floristic, vegetation structure and correlation with the distribution of tree species and soils of the riparian forest; dynamics of runoff; water physical-chemical aspects; and socio-economy aspects. These results indicate the strong structural drainage control of basin, however the current land use, dominated by cattle farm and deforestation, contribute to erosion. Furthermore, the riparian vegetation is in secondary successional stage probably due to preterit human disturbance. Soil and tree species correlation showed soil texture as attribute greater importance in the distribution of plant groups. The dynamics of runoff showed a low capacity of water storage basin. The water physical-chemical aspects results were directly related to the land use, and the parameters Color, Turbidity and Total Phosphorus presented themselves as the most suitable for monitoring water quality and environmental degradation. The basin is occupied by colonos from the process of private colonization occurred in the mid 1970 s and is predominated by small farms, many over-used, the average monthly income is directly related to its size. The failure of agriculture established at the time of colonization conditioned the uncontrolled deforestation for pasture and, since then, extensive cattle farming is predominant. Thus, the current land use, and the settlement historical processes of the region caused important environmental changes that are directly related to basin s sustainability, especially those related to water shortage. Therefore, it is necessary to implement recuperation and restructuring degraded areas program and the strengthening of family agriculture, aiming to economic and environmental sustainability.
Keywords: Ecologia; Florística; Comunidades vegetais; Amazônia Meridional; Recursos Hídricos; Bacias Hidrográficas; Alta Floresta (MT); Southern Amazon; Water Resources; Hydrographic Basin; Alta Floresta (MT); CIENCIAS BIOLOGICAS::ECOLOGIA